APLIKASI PENGENALAN POLA SEBAGAI MEDIA PEMBELAJARAN MENULIS PADA ANAK USIA DINI - Puteri Noraisya Primandari; Chaidir Chalaf Islam; Andreas Peter Chandra; Fahmi Muhammad (Universitas Islam Balitar, 2021)
Writing is part of the function of language as a means of communication. Writing in this case is certainly different from drawing or scribbling randomly. However, writing in the sense of writing a pen with a specific purpose is suitable, such as writing the letter 'a', then 'a' should not write 'd', 'p', 'q' or others. In today's technological developments, several mobile-based writing lessons have also begun to be introduced to children. However, some of the learning materials provided are still monotonous and do not provide correction for writing errors. Some of them only give examples of certain letters then the children imitate or give dotted lines on a letter then the children thicken the lines. This study takes a new approach, to create an integrated system that can correct children's writing so that it is correct. The system that will be developed is interactive in which the children write a letter and if it is correct, they will be given reward points and if it is wrong, they will be given feedback on the location of the error. For example a child wants to write the letter 'a' upside down or write 'a' with a line that is too long to become 'd', the system will give an error warning and the user can be able to write again.